2022
DOI: 10.2147/rmhp.s357654
|View full text |Cite
|
Sign up to set email alerts
|

Distributive Justice and Turnover Intention Among Medical Staff in Shenzhen, China: The Mediating Effects of Organizational Commitment and Work Engagement

Abstract: Background Turnover of medical staff is a vital issue in the global healthcare system. Previous evidence has confirmed the critical effect of distributive justice on turnover intention, but few studies have focused on the mediating mechanism behind this relationship or the medical staff. This study aimed to examine the mediating roles of organizational commitment and work engagement in the relationship between distributive justice and turnover intention of medical staff, and explore potential occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 47 publications
(53 reference statements)
0
10
1
Order By: Relevance
“…The results from the analysis indicated that three aspects of justice (distributive, procedural, and interpersonal) significantly and positively influenced turnover intention. These findings do not agree with our hypotheses and are inconsistent with most past research studies, where distributive justice ( Akgunduz and Cin, 2015 ; Yang et al, 2021 ; Chen et al, 2022 ), procedural justice ( Kumar, 2015 ; Gharbi et al, 2022 ), and interpersonal justice ( Leineweber et al, 2020 ) were mainly observed to affect turnover intention negatively.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The results from the analysis indicated that three aspects of justice (distributive, procedural, and interpersonal) significantly and positively influenced turnover intention. These findings do not agree with our hypotheses and are inconsistent with most past research studies, where distributive justice ( Akgunduz and Cin, 2015 ; Yang et al, 2021 ; Chen et al, 2022 ), procedural justice ( Kumar, 2015 ; Gharbi et al, 2022 ), and interpersonal justice ( Leineweber et al, 2020 ) were mainly observed to affect turnover intention negatively.…”
Section: Discussioncontrasting
confidence: 99%
“…However, it may be complete if we know how (the influencing mechanism through which) these organizational justice components could directly or indirectly influence turnover intentions. Job engagement has been proposed in previous studies (e.g., Park and Johnson, 2019;Cao et al, 2020;Jung et al, 2021;and Chen et al, 2022) to mediate the relationship between turnover intention and its antecedent significantly.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Healthcare workers’ perceptions of organizational justice significantly predict turnover intention [ 41 , 42 ] and job satisfaction [ 43 ]. The relationship between distributive justice and turnover intention has been mediated by organizational commitment and work engagement [ 44 ]. The organizational justice perceived by healthcare workers significantly and positively affects their organizational trust and organizational identification [ 45 ].…”
Section: Discussionmentioning
confidence: 99%